Muro-Neuro-Urodynamics ; a review of the functional assessment of mouse lower urinary tract function - Ito, Hiroki; Pickering, Anthony E.; Igawa, Yasuhiko; Kanai, Anthony; Fry, Christopher H.; Drake, Marcus J. (Frontiers in Physiology, 2017)
Background: Mouse urodynamic tests are fundamental to understanding normal lower urinary tract (LUT) function. These experiments also contribute to our understanding of neurological dysfunction, pathophysiological processes and potential mechanisms of therapy. Objectives: Systematic assessment of published evidence on urodynamics, advantages and limitations of different urodynamic measurements in mice, and consideration of potential implications for the clinical field. Methods: A search using specific search-terms for urodynamic studies and mice was conducted on PubMed (from inception to 1 July 2016). Results: We identified 55 studies examining or describing mouse neuro-urodynamics. We summarise reported features of mouse urodynamic function deriving from frequency-volume chart (FVC) measurements, voiding spot assays, filling cystometry and pressure-flow studies. Similarly, an influence of the diurnal cycle on voiding is observed in mice and should be considered when interpreting rodent urodynamic studies, especially FVC measurements and voiding spot assays. Anaesthesia, restraint conditions or filling rate influence mouse neuro-urodynamics. Mouse cystometric studies have observed intravesical pressure oscillations that accompany urine flow, attributed to high frequency opening and closing of the urethra. This characterisation is not seen in other species, except rats. In contrast to human clinical urodynamics, the terminology of these examinations has not been standardized although many rodent urodynamic studies have been described. Conclusion: Mice have many anatomical and physiological similarities to humans and they are generally cost effective, and allow investigation of the effects of ageing because of their short lifespan. There are some differences between mouse and human urodynamics. These must be considered when interpreting lower urinary tract function in mice, and translational value of murine disease models.